Lithium ion secondary battery

By regulating the distribution of the convex portions on the surface of the positive electrode sheet and the composition of the electrolyte, the first nitrile compound is used to inhibit the dissolution of the positive electrode cobalt element, the problem of deterioration of the performance of lithium-ion secondary batteries at high temperatures is solved, and higher circulation performance and storage are achieved Performance and security.

CN119481222APending Publication Date: 2025-02-18ZHUHAI COSMX BATTERY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411742048.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

While improving the energy density and power density of existing lithium-ion secondary batteries, it is difficult to avoid deterioration in high-temperature cycling performance, storage performance and safety performance.

Method used

By adjusting the orthogonal projection diameter and straight section length ratio of the convex portion on the surface of the positive electrode sheet, adjusting the density of the convex portion, optimizing the composition of the electrolyte, introducing a first nitrile compound containing 4-6 cyano groups, reducing dinitrile compound to inhibit the dissolution and side reaction of the positive electrode cobalt element.

Benefits of technology

It significantly improves the high-temperature cycling, storage and safety performance of lithium-ion secondary batteries, and avoids excessive dissolution of the positive electrode cobalt element and intensified side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481222A_ABST
    Figure CN119481222A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium ion secondary battery. The positive plate of the lithium ion secondary battery is provided with a first surface and a second surface along the thickness direction, the first surface is provided with a plurality of convex parts, and the second surface is provided with a plurality of concave parts; the diameter D1 of the orthographic projection of each convex part on the first surface and the length D2 of the straight section between any two convex parts meet the condition that D1 / D2 is 0.01-20; the electrolyte comprises a first nitrile compound with the chemical formula of # imgabs0 #, R0 is selected from at least one of # imgabs1 #, and the weight content of R0 in the electrolyte is 0.2%-3.5%; the weight content of the third nitrile compound in the electrolyte is less than or equal to 2%; the lithium ion secondary battery provided by the invention has good high-temperature cycle performance, high-temperature storage performance and safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art

[0002] With the rapid development of electric vehicles, mobile devices, energy storage systems and other fields, higher requirements are placed on the performance and safety of lithium-ion secondary batteries. The energy density and performance of lithium-ion secondary batteries can be improved by optimizing materials or optimizing the electrode structure. The performance of the positive electrode, as a key part of the lithium-ion secondary battery, directly affects the overall performance of the lithium-ion secondary battery. It is very important to avoid the degradation of its high-temperature cycle performance, high-temperature storage performance and safety performance while improving the energy density and power density of lithium-ion secondary batteries. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a lithium-ion secondary battery (hereinafter referred to as the battery), which regulates the distribution density of the protrusions on the first surface by regulating the ratio of the diameter of the orthographic projection of the protrusions formed on the first surface of the positive electrode sheet and the length of the straight section between any two protrusions, thereby regulating the liquid storage capacity of the positive electrode sheet and the contact area between the positive electrode sheet and the electrolyte; secondly, by regulating the composition of the electrolyte, a first nitrile compound containing 4-6 cyano groups is introduced into the electrolyte and the use of dinitrile compounds is greatly reduced, so as to inhibit the dissolution of the cobalt element in the positive electrode and improve the high-temperature stability, reduce the occurrence of side reactions, and improve the cycle performance, storage performance and safety performance of the battery at high temperatures.

[0004] In order to improve the energy density and power density of the battery, the present invention performs embossing treatment on the surface of the positive electrode sheet. After the positive electrode is embossed, the structural stability of the battery can be improved, the resistance and heat accumulation inside the battery can be reduced, and the possibility of safety risks such as short circuit and fire in the battery can be reduced; however, after the positive electrode is embossed, the contact area between the positive electrode sheet and the electrolyte is increased, resulting in the intensification of side reactions at high temperatures, resulting in increased dissolution of cobalt elements in the positive electrode, and the high-temperature cycle performance, high-temperature storage performance and safety performance of the battery are deteriorated. In order to alleviate the negative impact of positive electrode embossing, the inventors of the present invention can adjust the distribution density of the protrusions on the first surface by adjusting the ratio of the diameter of the positive projection of the protrusions on the first surface and the length of the straight section between any two protrusions, thereby improving the degree of electrolyte infiltration into the positive electrode sheet and the liquid retention of the positive electrode sheet, and preventing excessive electrolyte infiltration from causing aggravation of side reactions; however, it is difficult to effectively inhibit the dissolution of the cobalt element by simply adjusting the distribution of the protrusions on the surface of the positive electrode sheet. The dissolution of the cobalt element is usually inhibited by adding nitrile compounds to the electrolyte. The commonly used dinitrile compounds have short molecular chains, a small number of cyano groups, and poor structural stability. The inventors of the present invention have found through experimental studies that adding nitrile compounds containing 4-6 cyano groups to the electrolyte can not only optimize the electrolyte composition and reduce the risk of cobalt dissolution, but also greatly reduce the amount of dinitrile compounds in the electrolyte. This type of nitrile compound has good structural stability and strong complexing effect on transition metal ions, which can enhance the high temperature stability of the electrolyte and significantly improve the high temperature storage performance, high temperature cycle performance and safety of the battery.

[0005] Based on this, the inventor of the present invention proposes the following technical solution:

[0006] A lithium ion secondary battery comprises a positive electrode sheet and an electrolyte, wherein the positive electrode sheet has a first surface and a second surface along a thickness direction, wherein the first surface has a plurality of convex portions, and the second surface has a plurality of concave portions, wherein the concave portions and the convex portions have a corresponding positional relationship; the diameter of the orthographic projection of the convex portions on the first surface is D1, the length of a straight section between any two of the convex portions is D2, and D1 / D2 is 0.01-20;

[0007] The electrolyte comprises a chemical formula of A first nitrile compound, wherein R0 is selected from At least one of the following, R1 and R2 are each independently selected from a halogen-substituted or unsubstituted C1-C3 alkyl group, and m is an integer of 2-4; the weight content of the first nitrile compound in the electrolyte is A, and A is 0.2%-3.5%; the weight content of the third nitrile compound in the electrolyte is ≤2%, and the third nitrile compound includes at least one of succinonitrile, adiponitrile, and 1,2-bis(cyanoethoxy)ethane.

[0008] The technical solution proposed by the present invention has at least the following advantages compared with the prior art:

[0009] (1) In the present invention, the distribution density of the embossed protrusions on the positive electrode sheet is regulated by regulating the orthographic projection diameter of the protrusions formed on the positive electrode sheet after embossing and the ratio of the orthographic projection diameter of the protrusions on the first surface to the length of the straight section between any two protrusions, thereby adjusting the contact area between the positive electrode sheet and the electrolyte; at the same time, by optimizing the electrolyte composition and regulating the weight content of the first nitrile compound in the electrolyte, the occurrence of side reactions and the dissolution of the cobalt element in the positive electrode are suppressed, the complexation of transition metal ions is improved, and the positive electrode sheet is protected.

[0010] (2) In the present invention, the first nitrile compound reduces the amount of the third nitrile compound in the electrolyte, significantly improves the protective effect on the positive electrode sheet, alleviates the occurrence of side reactions between the positive electrode sheet surface and the electrolyte, and can improve the problems of high-temperature cycling and high-temperature storage caused by positive electrode embossing.

[0011] (3) In the present invention, the lithium ion secondary battery has good high temperature cycle performance, high temperature storage performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions therein, the following briefly introduces the drawings required for use in the descriptions of the embodiments and comparative examples. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0013] Figure 1 FIG. 4 is a schematic cross-sectional view of a positive electrode sheet along the thickness direction in one embodiment of the present invention.

[0014] Among them, 1 is the first surface, 2 is the positive electrode current collector, 3 is the second surface, 4 is the convex part, and 5 is the concave part. Specific implementation methods

[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0017] A lithium ion secondary battery comprises a positive electrode sheet and an electrolyte. The positive electrode sheet has a first surface and a second surface along a thickness direction. The first surface has a plurality of convex portions, and the second surface has a plurality of concave portions, and the concave portions correspond to the convex portions.

[0018] In the present invention, the diameter of the orthographic projection of the convex portion on the first surface is D1, the length of the straight section between two adjacent convex portions is D2, and D1 / D2 is 0.01-20, for example, 0.01, 0.04, 0.06, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.4, 0.5, 1, 2, 3, 4, 5, 6, 8, 10, 12, 14, 16, 18 or 20.

[0019] In one embodiment, D1 / D2 is 0.05-10.

[0020] In the present invention, the convex portion is obtained by embossing the surface of the positive electrode sheet, such as Figure 1 The figure shows a schematic cross-sectional view of a positive electrode sheet along the thickness direction in an embodiment of the present invention, wherein 1 is a first surface, 2 is a positive electrode current collector, 3 is a second surface, 4 is a convex portion, and 5 is a concave portion; it can be seen from the figure that after embossing treatment, a convex portion is formed on the first surface of the positive electrode sheet, and a concave portion is formed on the second surface of the positive electrode sheet.

[0021] In the present invention, the shape of the convex portion is not limited, for example: the concave portion and the convex portion are equivalent to the inner and outer surfaces of a sphere, the sphere is not limited to a hemisphere, and has a corresponding positional relationship on the positive electrode sheet; the "several" refers to a quantity ≥ 2.

[0022] In the present invention, the diameter of the orthographic projection of the convex portion on the first surface means: when the orthographic projection of the convex portion on the first surface is a regular circle, the diameter is the diameter of the circle; when the orthographic projection of the convex portion on the first surface is an irregular circle, the diameter is the equivalent diameter of a regular circle with the same area as the irregular circle. The length of the straight section means the shortest distance between any two points on the edges of adjacent convex portions.

[0023] In the present invention, the diameter of the projection of the convex portion on the first surface and the length of the straight section between two adjacent convex portions can be obtained by conventional testing methods in the art, for example, by combining a 3D microscope with image analysis software, selecting 10 convex portions on the 3D microscope image, measuring them separately and calculating their respective average values.

[0024] In the present invention, the positive electrode sheet is embossed to form the convex portion on the first surface. By adjusting the diameter of the positive projection of the convex portion on the first surface per unit area and the length of the straight section between two adjacent convex portions, it is beneficial to adjust the distribution of the convex portion on the first surface, thereby increasing the liquid storage capacity of the positive electrode sheet and the wettability of the electrolyte to the positive electrode sheet, which is beneficial to the positive electrode capacity, forms a good ion transmission path, and has a good buffering effect on the expansion of the negative electrode sheet.

[0025] In the present invention, the electrolyte comprises a chemical formula of A first nitrile compound, wherein R0 is selected from At least one of the following, R1 and R2 are each independently selected from a halogen-substituted or unsubstituted C1-C3 alkyl group, m is an integer of 2-4, for example, 2, 3 or 4; the "C1-C3 alkyl group" refers to an alkyl group having 1 to 3 carbon atoms.

[0026] In one embodiment, m=3.

[0027] In the present invention, the weight content of the first nitrile compound in the electrolyte is A, and A is 0.2%-3.5%, for example, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2% or 3.5%.

[0028] In one embodiment, A is 0.5%-2.5%.

[0029] In the present invention, although positive electrode embossing can improve the wettability of the electrolyte, when the positive electrode sheet is in excessive contact with the electrolyte, it will cause the side reaction to intensify, thereby increasing the dissolution of the cobalt element on the positive electrode sheet, especially under high temperature conditions, the high temperature cycle performance and high temperature storage performance of the battery are reduced. Nitrile compounds have the effect of inhibiting the dissolution of cobalt elements, and the commonly used nitrile compounds generally include dinitrile compounds, but the active sites of dinitrile compounds for complexing cobalt ions are limited, the effective utilization rate of cyano groups is not high, and the protection effect on the positive electrode is not good.

[0030] In the present invention, the inventor adopts a first nitrile compound to replace part or all of the dinitrile compound and introduce it into the electrolyte. The first nitrile compound has 4-6 cyano groups. Due to the longer chain structure and more cyano groups, its structure is more complex, and the intermolecular force is increased, so it has good thermal stability and structural stability; the first nitrile compound has more cyano groups, and the number of active sites that can complex transition metal ions is increased, which reduces the effect of transition metal ion dissolution (such as cobalt dissolution) on the positive electrode sheet, significantly improves the protective effect on the positive electrode sheet, alleviates the occurrence of side reactions between the surface of the positive electrode sheet and the electrolyte, and can improve the problems of high-temperature cycling and high-temperature storage caused by positive electrode embossing. However, the content of the first nitrile compound in the electrolyte is not the more the better. When A>3.5%, due to the excessive addition of the first nitrile compound, the impedance of the battery will increase and the polarization will increase.

[0031] In the present invention, the electrolyte optionally includes a third nitrile compound. Wherein, "optionally" means that the electrolyte may include the third nitrile compound or may not include the third nitrile compound, and the weight content of the third nitrile compound in the electrolyte is ≤2%, for example, 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%.

[0032] In the present invention, the third nitrile compound includes at least one of succinonitrile (SN), adiponitrile (AND), and 1,2-bis(cyanoethoxy)ethane (DENE).

[0033] In the present invention, the weight content of the third nitrile compound in the electrolyte can be measured by conventional testing methods in the art, such as testing by gas chromatography-mass spectrometry (GC-MS) or liquid chromatography (HPLC), and in the chromatographic test, it is identified by the difference between the peak time and the peak height, and then quantified by calibration.

[0034] In the present invention, D1 is 0.1mm-8mm, for example, 0.1mm, 0.2mm, 0.4mm, 0.6mm, 0.8mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, 6mm, 7mm or 8mm; D2 is 0.2mm-10mm, for example, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm, 4.5mm, 5mm, 6mm, 7mm, 8mm, 9mm or 10mm.

[0035] In the present invention, A, D1 and D2 satisfy: 0.05≤A / (D1 / D2)≤124, for example, 0.05, 0.06, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.4, 0.5, 1, 2, 3, 4, 5, 6, 8, 10, 12, 14, 16, 18, 20, 25, 30, 35, 40, 45, 50, 60, 65, 70, 80, 90, 100, 110, 120, 121, 122, 123 or 124.

[0036] In one embodiment, 0.25≤A / (D1 / D2)≤30.

[0037] In the present invention, the calculation of A / (D1 / D2) only takes the numerical parts of A, D2 and D1 for calculation, and the unit does not participate in the calculation. For example, when A=1%, D1=0.6mm, D2=1.5mm, A / (D1 / D2)=1 / (0.6 / 1.5)=2.5.

[0038] In the present invention, by regulating the weight content of the first nitrile compound in the electrolyte, the orthographic projection diameter of the convex portion on the first surface, and the length of the straight section between two adjacent convex portions, the degree of compatibility between the embossed positive electrode sheet and the electrolyte can be improved, so that the positive electrode embossing and the electrolyte cooperate with each other to improve the high temperature storage performance and high temperature cycle performance of the battery. When A / (D1 / D2) < 0.05, the distribution of the convex portion on the first surface per unit area is too dense, and more cobalt elements of the positive electrode are dissolved, while the addition amount of the first nitrile compound is too small, which is insufficient to complex the transition metal ions dissolved from the positive electrode surface, resulting in aggravated side reactions and deterioration of the battery's cycle performance; and when A / (D1 / D2) > 124, the distribution of the convex portion on the first surface is too sparse, the electrolyte has a poor wetting effect on the positive electrode sheet, and the capacity is insufficient. At the same time, the first nitrile compound is excessively added, resulting in increased impedance and polarization of the battery.

[0039] In the present invention, the convex portion is provided on the first surface, and the convex portion has a liquid storage effect and can store the electrolyte. In the early stage of the formation of the SEI film on the surface of the negative electrode, reducing the content of nitrile compounds in the electrolyte can reduce its damage to the negative electrode SEI film. In the later stage of the cycle, the electrolyte is released from the convex portion of the first surface, the nitrile compounds increase, and the transition metal ions dissolved from the positive electrode are more efficiently complexed, thereby reducing the occurrence of side reactions on the surface of the positive electrode.

[0040] In the present invention, the first nitrile compound comprises 4) At least one of .

[0042] In one embodiment, the first nitrile compound comprises At least one of .

[0043] In the present invention, the weight content of the first nitrile compound in the electrolyte can be measured by conventional testing methods in the art, such as testing by gas chromatography-mass spectrometry (GC-MC) or liquid chromatography (HPLC), and in the chromatographic test, it is identified by the difference between the peak time and the peak height, and then quantified by calibration.

[0044] In the present invention, the electrolyte further includes a second nitrile compound, which includes 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, glycerol trinitrile, 1,2,5-tris(cyanoethoxy)pentane and a chemical formula of At least one of the nitrile substances containing phosphoric acid ester, R'1, R'2, and R'3 are each independently selected from a halogen-substituted or unsubstituted C1-C6 alkyl group; similarly, the "C1-C6 alkyl group" refers to an alkyl group with 1 to 6 carbon atoms.

[0045] In one embodiment, the second nitrile compound includes at least one of 1,3,6-hexane trinitrile, glycerol trinitrile and the nitrile substance containing phosphoric acid ester.

[0046] In the present invention, the nitrile substance containing phosphoric acid ester includes

[0047] At least one of .

[0048] In one embodiment, the nitrile substance containing phosphoric acid ester includes 1).

[0049] In the present invention, the weight content of the second nitrile compound in the electrolyte is B, and B and A satisfy: 0.5≤B / A≤5.5, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.4, 2.8, 3.2, 3.6, 4, 4.5, 5 or 5.5.

[0050] In one embodiment, 0.8≤B / A≤3.

[0051] In the present invention, B is 0.5%-4.5%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.5%, 4% or 4.5%.

[0052] In one embodiment, B is 1.5%-3%.

[0053] In the present invention, a second nitrile compound is also introduced into the electrolyte, and the second nitrile compound contains three cyano groups. The spatial structure of the substance is better adapted to the electron cloud distribution of the cobalt ion, so that the coordination efficiency in the complex reaction of the transition metal ion is improved. Since the first nitrile compound has more cyano groups in its structure, it can provide more active sites for complex reaction. Therefore, the combination of the first nitrile compound and the second nitrile compound can effectively complex the transition metal ions dissolved from the positive terminal, reduce the catalytic oxidation of the transition metal ions to the electrolyte, and thus reduce the side reactions on the positive electrode surface. When B / A <0.5, the first nitrile compound is added excessively or the second nitrile compound is insufficient, so that the coordination efficiency of the complex reaction is low, and the internal resistance and polarization of the battery increase; when B / A>5.5, the first nitrile compound is insufficient, and the inhibitory effect on the dissolution of the cobalt element of the positive electrode is weak. The excessive addition of the second nitrile compound will increase the battery impedance, deteriorate the negative electrode interface, destroy the SEI film, and cause the side reactions between the electrolyte and the negative terminal to intensify, deteriorating the battery performance.

[0054] In the present invention, the weight content of the second nitrile compound in the electrolyte can be measured by conventional testing methods in the art, such as testing by gas chromatography-mass spectrometry (GC-MS) or liquid chromatography (HPLC), and in the chromatographic test, it is identified by the difference between the peak time and the peak height, and then quantified by calibration.

[0055] In the present invention, the height of the protrusion is h1, and h1 is 3μm-40μm, for example, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 24μm, 28μm, 32μm, 36μm, 38μm or 40μm.

[0056] In one embodiment, h1 is 5 μm-30 μm.

[0057] In the present invention, h1 and D1 satisfy 0.35≤h1 / D1≤100, for example, 0.35, 0.38, 0.4, 0.6, 0.8, 1, 1.5, 2, 2.5, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 95, 96, 97, 98, 99 or 100.

[0058] In one embodiment, 1.5≤h1 / D1≤85.7.

[0059] In the present invention, by adjusting the relationship between the height of the convex portion and the diameter of the orthographic projection of the convex portion on the first surface, the deformation space on the positive electrode sheet can be adjusted, the expansion of the negative electrode can be alleviated, and the amount of liquid storage can be adjusted. When h1 / D1<0.35, the height of the convex portion is large and the diameter of the orthographic projection of the convex portion on the first surface is too small, and the convex portion is sharp and easy to pierce the diaphragm; when h1 / D1>100, the height of the convex portion is small and the diameter of the orthographic projection of the convex portion on the first surface is too large, and the convex portion is flat and tends to be planarized when squeezed, and cannot effectively store liquid and improve the infiltration of electrolyte.

[0060] In the present invention, in the calculation of the ratio of h1 / D1, h1 and D1 are only substituted into the numerical part and the unit part does not participate in the calculation. For example, when h1=12μm and D1=0.6mm, h1 / D1=12 / 0.6=20.

[0061] In the present invention, regulating the diameter of the orthographic projection of the convex portion on the first surface and the length of the straight section between two adjacent convex portions has the effect of regulating the distribution density of the convex portions on the first surface, thereby being able to adjust the sum of the areas occupied by the convex portions on the first surface, so that the positive electrode sheet has a suitable deformation space, and at the same time adjusting the height of the convex portion, facing the cyclic expansion of the negative electrode, the convex portion has sufficient supporting force and deformation space, reducing the pressure of the negative electrode expansion on the positive electrode sheet; the convex portion has a good liquid storage effect, which can better reduce the generation of side reactions on the positive and negative electrode sheets.

[0062] In the present invention, the height of the protrusion can be obtained by conventional testing methods in the field, for example, by measuring with a micrometer, selecting 10 protrusions on the first surface, measuring their heights and calculating the average value to obtain the height of the protrusion. The above test results can also be obtained by other conventional testing methods in the field.

[0063] In the present invention, the height of the convex portion has a common meaning in the art, and refers to the maximum value of the vertical distance from any point on the convex portion to the first surface (the portion without concave portions and convex portions).

[0064] In the present invention, the electrolyte also includes a chemical formula The dicarbonate solvent is a dicarbonate solvent, wherein n is an integer of 0-2, for example, 0, 1 or 2.

[0065] In one embodiment, the dicarbonate solvent comprises and At least one of .

[0066] In yet another embodiment, the dicarbonate solvent comprises

[0067] In the present invention, the weight content of the dicarbonate solvent in the electrolyte is E, and E is 5%-30%, for example, 5%, 5.2%, 5.4%, 5.6%, 5.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%.

[0068] In one embodiment, E is 10%-20%.

[0069] In the present invention, adding a dicarbonate solvent to the electrolyte can improve the stability of the electrolyte. The dicarbonate solvent has high oxidation stability, which can improve the oxidation resistance of the electrolyte and reduce the oxidative decomposition of the electrolyte. Since the dicarbonate solvent has a longer carbon chain in its structure, its structural stability is higher than that of conventional carbonates. At the same time, its dielectric constant is lower, which can reduce the corrosive ions (PF6 - / F - ) migration rate, alleviate the corrosion of the positive electrode, further reduce the side reactions on the surface of the positive electrode, slow down the dissolution of cobalt ions, and improve the high-temperature cycle performance and high-temperature storage performance of the battery.

[0070] In the present invention, the weight content of the dicarbonate solvent in the electrolyte can be obtained by conventional testing methods in the art, such as gas chromatography (GC).

[0071] In the present invention, the electrolyte further comprises fluoroethylene carbonate (FEC), and the weight content of the fluoroethylene carbonate in the electrolyte is X, where X is 1%-30%, for example, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28% or 30%.

[0072] In one embodiment, X is 2%-20%.

[0073] In the present invention, X / A is 1-30, for example, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 9, 10, 12, 14, 16, 18, 20, 24, 28 or 30.

[0074] In one embodiment, X / A is 2-15.

[0075] In the present invention, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes Li a1 Ni b1 Co x1 Mn y1 M z1 O2, 0.9≤a1<1.1, 0≤b1<1, 0<x1≤1, 0≤y1≤1, 0≤z1≤0.05, M includes at least one of Al, Mg, Zr, Y, La and W.

[0076] In the present invention, the lithium-ion battery further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material.

[0077] In one embodiment, the silicon-based material includes at least one of silicon-oxygen, silicon-carbon material, elemental silicon and silicon alloy.

[0078] In one embodiment, the silicon-based material includes silicon-carbon material.

[0079] In the present invention, the negative electrode sheet includes silicon-carbon material, and the silicon-carbon negative electrode system can further improve the energy density of the battery. However, due to the significant volume expansion problem of silicon-carbon material during the cycle, although the positive electrode embossing can provide a certain deformation space to relieve the pressure on the positive electrode, it lacks protection for the silicon-carbon material. Therefore, by introducing a large amount of fluoroethylene carbonate (FEC) into the electrolyte, a LiF-rich SEI film can be effectively constructed to protect the silicon-carbon material; but when the content of FEC in the electrolyte is too high, the side reaction of the electrolyte is aggravated, resulting in gas production and interface degradation of the battery, so it is necessary to adjust the relationship between the weight fractions of the first nitrile compound and FEC in the electrolyte to reduce the generation of side reactions. When X / A>30, the FEC content in the electrolyte is too much or the content of the first nitrile compound is too little, which aggravates the occurrence of side reactions, causing battery gas production and battery performance degradation; when X / A<1, the FEC content in the electrolyte is insufficient or the content of the first nitrile compound is too high. The insufficient FEC content makes it difficult to form a complete, uniform and structurally stable SEI film on the negative electrode surface, and the protection effect on silicon-carbon materials is poor, and side reactions are aggravated. The high content of the first nitrile compound will increase the battery impedance and polarization, and deteriorate the high-temperature cycle and high-temperature storage performance of the battery.

[0080] In the present invention, the weight content of the FEC in the electrolyte can be obtained by conventional testing methods in the art, such as by gas chromatography-mass spectrometry (GC-MS).

[0081] In the present invention, the negative electrode active material further includes a carbon-based material, and the carbon-based material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon and soft carbon.

[0082] In the present invention, the electrolyte further comprises an organic solvent, and the organic solvent comprises at least one of fluorine-substituted or unsubstituted carbonate esters and carboxylates.

[0083] In one embodiment, the carbonate includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.

[0084] In one embodiment, the carboxylic acid ester includes at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-pentyl acetate, isopentyl acetate, ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate and ethyl n-butyrate.

[0085] In the present invention, the electrolyte also includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethylsulfonylimide), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium and lithium bis(trifluoromethylsulfonyl)imide.

[0086] In the present invention, the electrolyte further comprises an additive, and the additive comprises at least one of vinylene carbonate, vinyl ethylene carbonate, vinyl sulfate, 1,3-propane sultone and propenyl-1,3-sultone.

[0087] In the present invention, the lithium-ion secondary battery further comprises a separator, and the separator can be a separator conventionally used in the art, such as polyethylene.

[0088] In the present invention, the positive electrode sheet also includes a positive electrode collector, a positive electrode conductor and a positive electrode binder, and the negative electrode sheet also includes a negative electrode collector, a negative electrode conductor and a negative electrode binder. The positive electrode collector, positive electrode conductor, positive electrode binder, negative electrode collector, negative electrode conductor and negative electrode binder are all conventional choices made by those skilled in the art.

[0089] In the present invention, the charging cut-off voltage of the lithium-ion secondary battery is 4.45V or above.

[0090] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0091] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0092] In the following examples, unless otherwise specified, all materials used were commercially available analytically pure.

[0093] The following examples are used to illustrate the lithium ion secondary battery of the present invention.

[0094] Embodiment 1:

[0095] Preparation of electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a ratio of 3:2:3:10 to form an organic solvent; based on the total weight of the electrolyte, a first nitrile compound with a content of A (A is 2%, and the structural formula is shown in Ⅰ-1), FEC with a content of X (X is 15%), and an additive (2% of 1,3-propane sultone and 0.5% of vinyl sulfate based on the total weight of the electrolyte) are added to the organic solvent to form a mixed solvent; lithium hexafluorophosphate, a lithium salt, based on 11% of the total weight of the electrolyte, is added to the above mixed solvent, stirred evenly, and after passing the moisture and free acid tests, an electrolyte is obtained, wherein the sum of the weight contents of the organic solvent, the first nitrile compound, FEC, the lithium salt and the additive is 100%.

[0096] Among them, X / A=7.5.

[0097] Preparation of positive electrode:

[0098] The positive electrode active material (lithium cobalt oxide), conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on the front and back sides of the aluminum foil; the positive electrode sheet is obtained by drying and rolling; the positive electrode sheet is cut and processed by a special roller with protrusions to obtain a positive electrode sheet with a concave portion on one side and a convex portion on the other side;

[0099] The diameter D1 of the convex portion is 2 mm, the length D2 of the straight section between any two convex portions is 2 mm, the height h1 of the convex portion is 20 μm, D1 / D2 is 1, and h1 / D1 is 10.

[0100] At this time, A / (D1 / D2) is 2.

[0101] Preparation of negative electrode:

[0102] Artificial graphite, silicon-carbon material, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 78.5:20.5:0.5:0.25:0.25, deionized water is added, and the mixture is stirred thoroughly to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, and the negative electrode sheet is obtained after drying, rolling, cutting and washing.

[0103] Lithium-ion battery assembly:

[0104] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene film) are placed in order so that the separator is between the positive electrode sheet and the negative electrode sheet, and then the pole ears are welded and wound to obtain a core, which is then placed in an aluminum-plastic film packaging bag, followed by liquid injection, formation, secondary sealing and sorting processes to prepare a lithium-ion battery, and finally the electrical performance of the battery is tested.

[0105] Embodiment 2:

[0106] Preparation of the electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a ratio of 3:2:3:10 to form an organic solvent; based on the total weight of the electrolyte, a first nitrile compound having a content of A (A is 1.5%, and the structural formula is shown in Ⅰ-1) and a second nitrile compound having a content of B (B is 2.5%, wherein the second nitrile compound is composed of a phosphorus-containing compound having a structural formula of Ⅱ-1) are added to the organic solvent. A mixture of an organic solvent, a first nitrile compound and 1,3,6-hexanetrinitrile in a ratio of 1:1, FEC with a content of X (X is 15%), and an additive (2% of 1,3-propane sultone and 0.5% of vinyl sulfate based on the total weight of the electrolyte) is formed to form a mixed solvent; lithium hexafluorophosphate, a lithium salt, based on 11% of the total weight of the electrolyte is added to the mixed solvent, and the mixture is stirred evenly. After the moisture and free acid are tested to be qualified, an electrolyte is obtained, wherein the sum of the weight contents of the organic solvent, the first nitrile compound, the second nitrile compound, the FEC, the lithium salt and the additive is 100%.

[0107] Among them, B / A is 1.67 and X / A is 10.

[0108] Preparation of positive electrode:

[0109] The positive electrode active material (lithium cobalt oxide), conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on the front and back sides of the aluminum foil; the positive electrode sheet is obtained by drying and rolling; the positive electrode sheet is cut and processed by a special roller with protrusions to obtain a positive electrode sheet with a concave portion on one side and a convex portion on the other side;

[0110] The diameter D1 of the convex portion is 2 mm, the length D2 of the straight section between any two convex portions is 2 mm, the height h1 of the convex portion is 20 μm, D1 / D2 is 1, and h1 / D1 is 10.

[0111] At this time, A / (D1 / D2) is 1.5.

[0112] Preparation of negative electrode:

[0113] Artificial graphite, silicon-carbon material, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed evenly in a mass ratio of 78.5:20.5:0.5:0.25:0.25, deionized water is added, and the mixture is stirred thoroughly to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, and the negative electrode sheet is obtained after drying, rolling, cutting and washing.

[0114] Lithium-ion battery assembly:

[0115] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene film) are placed in order so that the separator is between the positive electrode sheet and the negative electrode sheet, and then the pole ears are welded and wound to obtain a core, which is then placed in an aluminum-plastic film packaging bag, followed by liquid injection, formation, secondary sealing and sorting processes to prepare a lithium-ion battery, and finally the electrical performance of the battery is tested.

[0116] Embodiment 3 group:

[0117] Example 3a is based on Example 1, except that the electrolyte and the positive electrode sheet are different, as follows:

[0118] Preparation of electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a ratio of 3:2:3:10 to form an organic solvent, and a dicarbonate solvent with a content of E (the structural formula is shown in III-1) is added based on the total weight of the electrolyte, and E is 14.5%, and the mixture is uniformly mixed to form a mixed solvent; based on the total weight of the electrolyte, a first nitrile compound with a content of A (A is 1.5%, the structural formula is shown in I-1), a second nitrile compound with a content of B (B is 2. 5%, wherein the second nitrile compound is obtained by mixing a phosphoric acid ester nitrile substance of structural formula Ⅱ-1 and 1,3,6-hexanetrinitrile in a ratio of 1:1), FEC with a content of X (X is 15%), and an additive (2% of 1,3-propane sultone and 0.5% of vinyl sulfate based on the total weight of the electrolyte) to form a mixed solvent; lithium hexafluorophosphate, a lithium salt, based on 11% of the total weight of the electrolyte is added to the above mixed solvent, stirred evenly, and after passing the moisture and free acid tests, an electrolyte is obtained, wherein the sum of the weight contents of the organic solvent, the dicarbonate solvent, the first nitrile compound, the second nitrile compound, the FEC, the lithium salt and the additive is 100%.

[0119] Among them, B / A is 1.67 and X / A is 10.

[0120] Preparation of positive electrode:

[0121] The positive electrode active material (lithium cobalt oxide), conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on the front and back sides of the aluminum foil; the positive electrode sheet is obtained by drying and rolling; the positive electrode sheet is cut and processed by a special roller with protrusions to obtain a positive electrode sheet with a concave portion on one side and a convex portion on the other side;

[0122] The diameter D1 of the convex portion is 2 mm, the length D2 of the straight section between any two convex portions is 2 mm, the height h1 of the convex portion is 20 μm, D1 / D2 is 1, and h1 / D1 is 10.

[0123] At this time, A / (D1 / D2) is 1.5.

[0124] Example 3b is based on Example 1, except that the electrolyte and the positive electrode sheet are different, as follows:

[0125] Preparation of electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a ratio of 3:2:3:10 to form an organic solvent, and a dicarbonate solvent having a content of E (the structural formula is shown in III-1) is added based on the total weight of the electrolyte, where E is 20%, and the mixture is uniformly mixed to form a mixed solvent; based on the total weight of the electrolyte, a first nitrile compound having a content of A (A is 2.5%, the structural formula is shown in I-1) and a second nitrile compound having a content of B (B is 2%) are added to the mixed solvent. , wherein the second nitrile compound is obtained by mixing a phosphoric acid ester nitrile substance of structural formula Ⅱ-1 and 1,3,6-hexanetrinitrile in a ratio of 1:2), FEC with a content of X (X is 15%), and an additive (2% of 1,3-propane sultone and 0.5% of vinyl sulfate based on the total weight of the electrolyte) to form a mixed solvent; lithium hexafluorophosphate, a lithium salt, based on 11% of the total weight of the electrolyte is added to the above mixed solvent, stirred evenly, and after passing the moisture and free acid tests, an electrolyte is obtained, wherein the weight content of the organic solvent, the dicarbonate solvent, the first nitrile compound, the second nitrile compound, the FEC, the lithium salt and the additive sums up to 100%.

[0126] Among them, B / A is 0.8 and X / A is 6.

[0127] Preparation of positive electrode:

[0128] The positive electrode active material (lithium cobalt oxide), conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on the front and back sides of the aluminum foil; the positive electrode sheet is obtained by drying and rolling; the positive electrode sheet is cut and processed by a special roller with protrusions to obtain a positive electrode sheet with a concave portion on one side and a convex portion on the other side;

[0129] The diameter D1 of the convex portion is 2 mm, the length D2 of the straight section between any two convex portions is 0.2 mm, the height h1 of the convex portion is 5 μm, D1 / D2 is 10, and h1 / D1 is 2.5.

[0130] At this time, A / (D1 / D2) is 0.25.

[0131] Example 3c is based on Example 1, except that the electrolyte and the positive electrode sheet are different, as follows:

[0132] Preparation of the electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a ratio of 3:2:3:10 to form an organic solvent, and a dicarbonate solvent having a content of E (the structural formula is shown in III-1) is added based on the total weight of the electrolyte, where E is 10%, and the mixture is uniformly mixed to form a mixed solvent; based on the total weight of the electrolyte, a first nitrile compound having a content of A (A is 1.5%, the structural formula is shown in Ⅰ-1) and a second nitrile compound having a content of B (B The invention relates to a method for preparing an electrolyte comprising: forming a first nitrile compound having a phosphoric acid ester nitrile substance of structural formula Ⅱ-1 and 1,3,6-hexanetrinitrile in a ratio of 3:2, FEC having a content of X (X being 20%), and an additive (2% of 1,3-propane sultone and 0.5% of vinyl sulfate based on the total weight of the electrolyte) to form a mixed solvent; adding lithium hexafluorophosphate, a lithium salt, based on 11% of the total weight of the electrolyte, to the mixed solvent, stirring evenly, and obtaining an electrolyte after passing the moisture and free acid tests, wherein the sum of the weight contents of the organic solvent, the first nitrile compound, the second nitrile compound, FEC, the lithium salt and the additive is 100%.

[0133] Among them, B / A is 1 and X / A is 13.33.

[0134] Preparation of positive electrode:

[0135] The positive electrode active material (lithium cobalt oxide), conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on the front and back sides of the aluminum foil; the positive electrode sheet is obtained by drying and rolling; the positive electrode sheet is cut and processed by a special roller with protrusions to obtain a positive electrode sheet with a concave portion on one side and a convex portion on the other side;

[0136] The diameter D1 of the convex portion is 0.35 mm, the length D2 of the straight section between any two convex portions is 7 mm, the height h1 of the convex portion is 30 μm, D1 / D2 is 0.05, and h1 / D1 is 85.7.

[0137] At this time, A / (D1 / D2) is 30.

[0138] Embodiment 3d is based on Embodiment 1, except that the electrolyte and the positive electrode sheet are different, as follows:

[0139] Preparation of the electrolyte: In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a ratio of 3:2:3:10 to form an organic solvent, and a dicarbonate solvent having a content of E (the structural formula is shown in III-1) is added based on the total weight of the electrolyte, where E is 18.5%, and the mixture is uniformly mixed to form a mixed solvent; based on the total weight of the electrolyte, a first nitrile compound having a content of A (A is 1%, the structural formula is shown in Ⅰ-1) and a second nitrile compound having a content of B (B is 3 %, wherein the second nitrile compound is obtained by mixing a phosphoric acid ester nitrile substance of structural formula Ⅱ-1, 1,3,6-hexane trinitrile and glycerol trinitrile in a ratio of 3:5), FEC with a content of X (X is 10%), and additives (2% of 1,3-propane sultone and 0.5% of vinyl sulfate based on the total weight of the electrolyte) to form a mixed solvent; lithium hexafluorophosphate, a lithium salt, based on 11% of the total weight of the electrolyte is added to the above mixed solvent, stirred evenly, and after passing the moisture and free acid tests, an electrolyte is obtained, wherein the sum of the weight contents of the organic solvent, the first nitrile compound, the second nitrile compound, FEC, the lithium salt and the additive is 100%.

[0140] Among them, B / A is 3 and X / A is 10.

[0141] Preparation of positive electrode:

[0142] The positive electrode active material (lithium cobalt oxide), conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on the front and back sides of the aluminum foil; the positive electrode sheet is obtained by drying and rolling; the positive electrode sheet is cut and processed by a special roller with protrusions to obtain a positive electrode sheet with a concave portion on one side and a convex portion on the other side;

[0143] The diameter D1 of the convex portion is 4.5 mm, the length D2 of the straight section between any two convex portions is 4 mm, the height h1 of the convex portion is 10 μm, D1 / D2 is 1.125, and h1 / D1 is 2.2.

[0144] At this time, A / (D1 / D2) is 0.89.

[0145] Embodiment 4 group:

[0146] This group of examples is used to verify the influence of the ratio of "D1 / D2", which is achieved by changing D1 and D2. Based on Example 1, the difference is that the positive electrode sheet is different, as follows:

[0147] Example 4a is based on Example 3a, except that the diameter D1 of the protrusion on the positive electrode sheet is 7.95 mm, the length D2 of the straight section between any two protrusions is 0.4 mm, and the height h1 of the protrusion is 20 μm; D1 / D2 is 19.9, h1 / D1 is 2.52, and at this time, A / (D1 / D2) is 0.08.

[0148] Example 4b is based on Example 3a, except that the diameter D1 of the protrusion on the positive electrode sheet is 0.12 mm, the length D2 of the straight section between any two protrusions is 9.9 mm, and the height h1 of the protrusion is 20 μm; D1 / D2 is 0.012, h1 / D1 is 166.7, and at this time, A / (D1 / D2) is 123.75.

[0149] Embodiment 5 group:

[0150] This group of examples is used to verify the influence of the ratio of "A / (D1 / D2)", which is achieved by changing D1, D2 and A. It is based on Example 3a, and the difference is that the positive electrode sheet and the electrolyte are different, as follows:

[0151] Example 5a, based on Example 3a, differs in that, for the electrolyte, the content A of the first nitrile compound is 1%; wherein B / A is 2.5, and X / A is 15;

[0152] For the positive electrode sheet, the diameter D1 of the protrusion is 2 mm, and the length D2 of the straight section between any two protrusions is 0.2 mm; D1 / D2 is 10, h1 / D1 is 10, and at this time, A / (D1 / D2) is 0.1.

[0153] Example 5b is based on Example 3a, except that, for the electrolyte, the content A of the first nitrile compound is 2.5%; wherein B / A is 1, and X / A is 6;

[0154] For the positive electrode sheet, the diameter D1 of the protrusion is 0.35 mm, and the length D2 of the straight section between any two protrusions is 7 mm; D1 / D2 is 0.05, h1 / D1 is 57.14, and at this time, A / (D1 / D2) is 50.

[0155] Example 5c is based on Example 3a, except that, for the electrolyte, the content A of the first nitrile compound is 0.5%; wherein B / A is 5, and X / A is 30;

[0156] At this time, A / (D1 / D2) is 0.5.

[0157] Example 5d is based on Example 3a, except that, for the electrolyte, the content A of the first nitrile compound is 3.5%; wherein B / A is 0.71, and X / A is 4.29;

[0158] At this time, A / (D1 / D2) is 3.5.

[0159] Embodiment 6 group:

[0160] This group of examples is used to verify the influence of the ratio of "B / A" and the material selection of the second nitrile compound, which is achieved by changing B and A or changing the type of the second nitrile compound. Based on Example 3a, the difference is that the electrolyte is different, as follows:

[0161] Example 6a is based on Example 3a, except that, based on the total weight of the electrolyte, the content of the first nitrile compound A is 2.5%, the content of the second nitrile compound B is 1.5%, B / A is 0.6, and X / A is 6; at this time, A / (D1 / D2) is 2.5.

[0162] Example 6b is based on Example 3a, except that, based on the total weight of the electrolyte, the content of the first nitrile compound A is 1.5%, the content of the second nitrile compound B is 0.5%, B / A is 0.33, and X / A is 10; at this time, A / (D1 / D2) is 1.5.

[0163] Example 6c is based on Example 3a, except that, based on the total weight of the electrolyte, the content of the first nitrile compound A is 1.5%, the content of the second nitrile compound B is 4.5%, B / A is 3, and X / A is 10; at this time, A / (D1 / D2) is 1.5.

[0164] Example 6d is based on Example 3a, except that the second nitrile compound is obtained by mixing a phosphoric acid ester nitrile substance of structural formula II-1, 1,3,6-hexane trinitrile and glycerol trinitrile in a ratio of 1:1:1.

[0165] Example 6e is based on Example 3a, and differs in that the second nitrile compound is obtained by mixing a phosphoric acid ester nitrile substance of structural formula II-1, 1,3,6-hexane trinitrile and glycerol trinitrile in a ratio of 1:2:1.

[0166] Embodiment 7 group:

[0167] This group of examples is used to verify the effects of the amount and type of dicarbonate solvent added, which is achieved by changing the value of E or changing the material selection of the dicarbonate solvent. Based on Example 3a, the difference is that the electrolyte is different, as follows:

[0168] Example 7a is based on Example 3a, except that the content E of the dicarbonate solvent (structural formula shown in III-1) is 4.97% based on the total weight of the electrolyte.

[0169] Example 7b is based on Example 3a, except that the content E of the dicarbonate solvent (structural formula shown in III-1) is 29.6% based on the total weight of the electrolyte.

[0170] Example 7c is based on Example 3a, except that the dicarbonate solvent is a substance having the structural formula III-2.

[0171] Embodiment 8 group:

[0172] This group of examples is used to verify the influence of the ratio of "X / A", which is achieved by changing X and A. It is based on Example 3a, and the difference is that the electrolyte is different, as follows:

[0173] Example 8a is based on Example 3a, except that, based on the total weight of the electrolyte, the content of the first nitrile compound A is 1%, the content of FEC X is 20%, B / A is 2.5, and X / A is 20; at this time, A / (D1 / D2) is 1.

[0174] Example 8b is based on Example 3a, except that, based on the total weight of the electrolyte, the content of the first nitrile compound A is 2.5%, the content of FEC X is 10%, B / A is 1, and X / A is 4; at this time, A / (D1 / D2) is 2.5.

[0175] Example 8c is based on Example 3a, except that, based on the total weight of the electrolyte, the content of the first nitrile compound A is 1.5%, the content of FEC X is 35%, B / A is 1.7, and X / A is 23.33; at this time, A / (D1 / D2) is 1.5.

[0176] Embodiment 9:

[0177] The selection of the first nitrile compound in the electrolyte is changed, based on Example 3a, the difference being that the first nitrile compound in the electrolyte is a substance with structural formula as shown in Ⅰ-2.

[0178] Example 10 Group:

[0179] This group of examples is used to verify the influence of the ratio of "h1 / D1", which is achieved by changing h1 and D1. It is based on Example 3a, and the difference is that the positive electrode sheet is different, as follows:

[0180] Example 10a is based on Example 3a, and its difference is that, for the positive electrode sheet, the diameter D1 of the protrusion is 8 mm, the length D2 of the straight section between any two protrusions is 8 mm, the height h1 of the protrusion is 3 μm; and h1 / D1 is 0.38.

[0181] Example 10b is based on Example 3a, and its difference is that, for the positive electrode sheet, the diameter D1 of the protrusion is 0.4 mm, the length D2 of the straight section between any two protrusions is 0.4 mm, the height h1 of the protrusion is 39.8 μm, and h1 / D1 is 99.5.

[0182] Embodiment 11:

[0183] Based on Example 3a, the difference is that based on the total weight of the electrolyte, the content of the third nitrile compound is 0.5%, wherein the third nitrile compound is succinonitrile, and the sum of the weight contents of the organic solvent, the dicarbonate solvent, the first nitrile compound, the second nitrile compound, the third nitrile compound, FEC, the lithium salt and the additive in the electrolyte is 100%.

[0184] Comparative Example 1:

[0185] This group of comparative examples is used to verify the addition amount of the first nitrile compound and the effect of replacing the dinitrile compound with the first nitrile compound, as follows:

[0186] Comparative Example 1a is based on Example 1, except that, based on the total weight of the electrolyte, the content of the first nitrile compound A is 0%, the content of the third nitrile compound is 2.5%, wherein the third nitrile compound is adiponitrile, and the sum of the weight contents of the organic solvent, the third nitrile compound, FEC, the lithium salt and the additive in the electrolyte is 100%.

[0187] Comparative Example 1b is based on Example 2, except that, based on the total weight of the electrolyte, the content of the first nitrile compound A is 4%, X / A is 3.75, and B / A is 0.625; at this time, A / (D1 / D2) is 4.

[0188] Comparative Example 2 Group:

[0189] This set of comparative examples is used to verify the influence of the ratio of "D1 / D2", which is achieved by changing the diameter of the orthographic projection of the convex portion on the first surface and the length of the straight section between any two convex portions, as follows:

[0190] Comparative Example 2a is based on Example 3a, except that, for the positive electrode sheet, the diameter D1 of the protrusion is 0.05 mm, and the length D2 of the straight section between any two protrusions is 12 mm. At this time, D1 / D2 is 0.004, h1 / D1 is 400, and A / (D1 / D2) is 360.

[0191] Comparative Example 2b is based on Example 3a, except that, for the positive electrode sheet, the diameter D1 of the protrusion is 10 mm, and the length D2 of the straight section between any two protrusions is 0.1 mm. At this time, D1 / D2 is 200, h1 / D1 is 2, and A / (D1 / D2) is 0.01.

[0192] Comparative Example 2c is based on Example 3a, except that, for the positive electrode sheet, the diameter D1 of the protrusion is 7 mm, and the length D2 of the straight section between any two protrusions is 0.3 mm. At this time, D1 / D2 is 23.33, h1 / D1 is 2.86, and A / (D1 / D2) is 0.06.

[0193] Test example:

[0194] (1) 60℃ storage test:

[0195] The battery obtained in the embodiment and comparative example was adjusted to 50% SOC in a constant temperature environment of 25°C. The initial thickness T1 of the battery was tested at the time of delivery. The battery was charged to an upper limit voltage of 4.48V at a constant current and constant voltage of 0.7C, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C. The capacity obtained by discharge was the initial capacity C1. The battery was charged to an upper limit voltage at a constant current and constant voltage of 0.7C, with a cut-off current of 0.05C. The fully charged battery was stored in a constant temperature environment of 60°C, and the thermal thickness expansion change of the battery was monitored. The battery was limited to obvious bulging or thermal thickness expansion of >20%. The final thermal thickness T2 of the battery stored at 60°C was tested. The thickness expansion rate of the lithium battery stored at 60°C = (T2-T1) / T1×100%.

[0196] (2) 45℃ floating charge test:

[0197] The battery obtained from the embodiment and the comparative example is placed in a constant temperature environment of 25°C, and its charge is adjusted to 50% SOC. The initial thickness T1 of the battery is tested when the material is received. The battery is placed in a constant temperature environment of 45°C, and charged to 4.48V at 0.5C constant current and constant voltage. One cycle is 5 days of constant voltage charging. The thermal thickness expansion change of the battery is monitored. The final hot thickness T2' of the battery after 45°C float charge is tested with obvious inflation of the battery as the limiting condition. The battery 45°C float charge thickness expansion rate = (T2'-T1) / T1×100%.

[0198] (3) 130℃ hot box test:

[0199] After the battery is fully charged at 0.5C constant current and constant voltage, it is placed in a constant temperature box and heated by convection or circulating hot air box with a starting temperature of 20±5℃. The temperature of the hot box is increased to 130±2℃ at a rate of 5±2℃ per minute and maintained at this temperature for 30 minutes before the test is terminated.

[0200] Judgment standard: The battery does not catch fire or explode within 30 minutes.

[0201] (4) Overcharge test:

[0202] 3C-5V overcharge test: Under the condition of ambient temperature (25±5)℃, charge the discharged battery with 3C constant current to 5.0V, then change to constant voltage charging. The charging time is limited to 7H or the charging is stopped when the battery surface temperature is stable (temperature difference within 45min ≤2℃).

[0203] Judgment criteria: The battery does not catch fire or explode.

[0204] (5) 45℃ cycle test:

[0205] After measuring the OCV, the battery with 50% SOC is first tested for voltage, internal resistance, and thickness T1. Then the battery is placed in a 45°C constant temperature environment for charge and discharge test at a rate of 0.7C / 0.5C, with a cut-off voltage range of 3.0V-4.48V, and the charge and discharge cycle is 500 times. The cycle discharge capacity is recorded and divided by the discharge capacity of the first cycle to obtain the high-temperature cycle capacity retention rate. After 500 cycles, the fully charged battery is taken out of the 45°C constant temperature box and immediately tested for its hot fully charged thickness T2 after 500 cycles. The 500th cycle capacity retention rate and the cycle thickness expansion rate of the battery when it is cycled 500 times are recorded respectively. Among them, the thickness expansion rate (%) = (T2-T1) / T1×100%.

[0206] The test results of the test case are shown in Table 1:

[0207] Table 1:

[0208]

[0209] It can be seen from Table 1 that the lithium ion battery prepared by the present invention has good high temperature cycle performance, high temperature storage performance and safety compared with the comparative example.

[0210] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The invention comprises a positive electrode sheet and an electrolyte, wherein the positive electrode sheet has a first surface and a second surface along a thickness direction, wherein the first surface has a plurality of convex portions, and the second surface has a plurality of concave portions, and the convex portions correspond to the concave portions; The diameter of the orthographic projection of the convex portion on the first surface is D1, the length of the straight section between any two convex portions is D2, and D1 / D2 is 0.01-20; The electrolyte comprises a chemical formula of A first nitrile compound, wherein R0 is selected from At least one of, R1 and R2 are each independently selected from halogen-substituted or unsubstituted C1-C3 alkyl, and m is an integer of 2-4; The weight content of the first nitrile compound in the electrolyte is A, and A is 0.2%-3.5%; The weight content of the third nitrile compound in the electrolyte is ≤2%, and the third nitrile compound includes at least one of succinonitrile, adiponitrile, and 1,2-bis(cyanoethoxy)ethane.

2. The lithium ion secondary battery according to claim 1, wherein 0.05≤A / (D1 / D2)≤124, preferably 0.25≤A / (D1 / D2)≤30.

3. The lithium ion secondary battery according to claim 1 or 2, wherein D1 / D2 is 0.05-10; and / or, D1 is 0.1 mm to 8 mm, and D2 is 0.2 mm to 10 mm; And / or, A is 0.5%-2.5%.

4. The lithium ion secondary battery according to claim 3, wherein: The first nitrile compound comprises At least one of; Preferably At least one of .

5. The lithium ion secondary battery according to claim 1, wherein The electrolyte also includes a second nitrile compound, which includes 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, glycerol trinitrile, 1,2,5-tris(cyanoethoxy)pentane and a chemical formula of At least one of the nitrile substances containing phosphoric acid ester, R'1, R'2, R'3 are each independently selected from halogen-substituted or unsubstituted C1-C6 alkyl; Preferably, the second nitrile compound includes at least one of 1,3,6-hexane trinitrile, glycerol trinitrile and the nitrile substance containing phosphoric acid ester.

6. The lithium ion secondary battery according to claim 5, wherein: The weight content of the second nitrile compound in the electrolyte is B, and B and A satisfy: 0.5≤B / A≤5.5, preferably 0.8≤B / A≤3; And / or, B is 0.5%-4.5%, preferably 1.5%-3%.

7. The lithium ion secondary battery according to claim 1, wherein The height of the convex portion is h1, and h1 is 3 μm-40 μm, preferably 5 μm-30 μm; And / or, h1 and D1 satisfy 0.35≤h1 / D1≤100; preferably 1.5≤h1 / D1≤85.

7.

8. The lithium ion secondary battery according to claim 1, wherein The electrolyte comprises a chemical formula of A dicarbonate solvent, n is an integer of 0-2; preferably, the dicarbonate solvent includes At least one of; And / or, the weight content of the dicarbonate solvent in the electrolyte is E, and E is 5%-30%, preferably 10%-20%.

9. The lithium ion secondary battery according to claim 1, wherein The electrolyte further comprises fluoroethylene carbonate, the weight content of the fluoroethylene carbonate in the electrolyte is X, X is 1%-30%, preferably 2%-20%; And / or, X / A is 1-30, preferably 2-15.

10. The lithium ion secondary battery according to claim 1, wherein The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes Li a1 Ni b1 Co x1 Mn y1 M z O2, 0.9≤a1<1.1, 0≤b1<1, 0<x1≤1, 0≤y1≤1, 0≤z1≤0.05, M includes at least one of Al, Mg, Zr, Y, La and W; And / or, the lithium-ion battery further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material; Preferably, the silicon-based material includes silicon-carbon material.

Citation Information

Patent Citations

  • Electricity storage device and electronic apparatus

    CN116706239A

  • Electrochemical device and electronic device

    CN116802877A

  • Battery

    CN117810553A

  • Electrolyte and application thereof

    CN118970173A

  • Battery

    CN221841870U